Epidermal Growth Factor Pathway in the Age-Related Decline of Oligodendrocyte Regeneration - Rivera, Andrea D.; Azim, Kasum; Macchi, Veronica; Porzionato, Andrea; Butt, Arthur M.; De Caro, Raffaele (Frontiers in Cellular Neuroscience, 2022)
Oligodendrocytes (OLs) are specialised glial cells that myelinate CNS axons. OLs are generated throughout life from oligodendrocyte progenitor cells (OPCs) via a series of tightly controlled differentiation steps. Life-long myelination is essential for learning and to replace myelin lost through pathology, such as multiple sclerosis (MS) and Alzheimer’s disease (AD). Notably, there is considerable myelin loss in the aging brain, which is accelerated in AD and underpins the failure of remyelination in secondary progressive MS. An important factor in age-related myelin loss is a marked decrease in the regenerative capacity of OPCs. In this review, we will contextualise recent advances in the key role of Epidermal Growth Factor (EGF) signalling in regulating multiple biological pathways in oligodendroglia that are dysregulated in aging.